1983
DOI: 10.1295/polymj.15.625
|View full text |Cite
|
Sign up to set email alerts
|

DC Electrical Conductivity of Cellulose

Abstract: ABSTRACT:DC electrical conductivity was measured from room temperature to about 230°C for Cellulose I and Cellulose II. The conductivity vs. temperature curve showed a break at about l 50°C for Cell I and at about 80°C for Cell II. The break points corresponded to those observed previously in the spacing vs. temperature curves. These phenomena may possibly be assoc-iated with the second order transition at which the restricted motion of chain segments in the crystals begins to acquire high mobility. The conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Over a decade after this cluster of early studies, Crofton and Patrick studied the conductivity of cellulose, cellulose acetate, and ethyl cellulose with various water contents, experimentally verifying the hopping conduction mechanism at elevated temperature (Crofton and Patrick, 1981). In another study, the conductivity was reported to increase faster at higher temperature (>150°C) in wood-derived cellulose (Betula tauschii, or Japanese white birch), attributed to a second order phase transition after which the breaking of hydrogen bonds results in increased thermal motion (Takahashi and Takenaka, 1983).…”
Section: Cellulose-based Pems Pristine Cellulosic Materialsmentioning
confidence: 98%
“…Over a decade after this cluster of early studies, Crofton and Patrick studied the conductivity of cellulose, cellulose acetate, and ethyl cellulose with various water contents, experimentally verifying the hopping conduction mechanism at elevated temperature (Crofton and Patrick, 1981). In another study, the conductivity was reported to increase faster at higher temperature (>150°C) in wood-derived cellulose (Betula tauschii, or Japanese white birch), attributed to a second order phase transition after which the breaking of hydrogen bonds results in increased thermal motion (Takahashi and Takenaka, 1983).…”
Section: Cellulose-based Pems Pristine Cellulosic Materialsmentioning
confidence: 98%
“…In this sense, paper electrophoresis is less prone to heat generation than agarose gel electrophoresis because nitrocellulose membrane has 10 9 -fold higher resistivity than agarose gel, and therefore it provides higher resistance to current. 24,25 The core of PEB is based on paper electrophoresis, which since 1950s has been developing strategies for the examination of a variety of different samples, ranging from water to human serum. [26][27][28] Most of those works aimed at the separation of target analytes (including inorganic salts, amino acids, enzymes and proteins) along a filter paper and their subsequent analysis, such as the measurement of their concentration and/or specific activity.…”
Section: Conceptmentioning
confidence: 99%
“…Javadi et al [ 393] Hydrogel composite of PU, PEDOT:PSS, and liquid crystal graphene oxide ReN-CX human NSCs ±0.25 mA cm −2 biphasic waveform of 100 μs with 20 μs interphase at 250 Hz…”
Section: Gupta Et Al Compared the Effects Of Incorporating Multi-walledmentioning
confidence: 99%